Hospice and End-of-Life Care for Chronic Patients in an Aging Society: A Necessity for the Future - Dehghannezhad, Javad (Advances in Nursing & Midwifery, 2022)
INTRODUCTION End-of-life care helps all people with advanced, progressive, and incurable diseases [1]. Live in the best conditions until death and have a "Good Death" when dying [2]. Palliative care is an approach that can identify and respond to the needs of patients and their families at the end of life [3]. Nevertheless, only 37% of the countries of the world consider palliative care as a national policy [4] and according to the World Health Organization, patients that need to palliative care include cardiovascular diseases (38.5%), cancer (34%), chronic pulmonary diseases (10.3%), HIV (5.7%), and diabetes (4.6%) [5]. Palliative care is performed in a variety of models, one of these models is Hospice care [6]. Hospices provide care for people from the point at which their illness is diagnosed as terminal to the end of their life, however long that may be [7]. There is ample evidence to support a higher quality of life in hospice patients compared with terminally ill patients in the hospital setting. Numerous studies evaluating quality of end of life in settings other than the hospital show that family members are consistently more likely to report a favorable dying experience of the decedent when hospice or palliative care is chosen, compared with hospitalization [8]. It is also important to pay attention to human dignity in the hospice and Themes of dying with dignity are as follows: a human right, autonomy and independence, relieved symptom distress, respect, being human and being self, meaningful relationships, dignified treatment and care, existential satisfaction, privacy, and calm environment [9].